Facile preparation of toluidine blue-loaded DNA nanogels for anticancer photodynamic therapy - Guo, Hua; Wang, Huimin; Deng, Hong; Zhang, Yiyi; Yang, Xue; Zhang, Weiqi (Frontiers in Bioengineering and Biotechnology, 2023)
Photodynamic therapy (PDT) provides an effective therapeutic alternative for many types of cancer in addition to the surgery, radiation and chemotherapy. The PDT treatment outcome is largely defined by both the light and dark toxicity of photosensitizers (PS), which can be technically improved with the assistance of drug delivery system especially the nanocarriers. Toluidine blue (TB) is a representative PS that demonstrates high PDT efficacy, however its application is largely limited by the associated dark toxicity. Inspired by TB’s noncovalent binding with nucleic acids, here we demonstrated the DNA nanogel (NG) could serve as an effective TB delivery vehicle to facilitate anticancer PDT. The DNA/TB NG was constructed by the simple self-assembly between TB and short DNA segments using cisplatin as a crosslinker. Compared with TB alone, DNA/TB NG displayed a controlled TB releasing behavior, effective cellular uptake and phototoxicity while a reduced dark toxicity in breast cancer cells MCF-7, thus represented a promising strategy to improve the TB-mediated PDT for cancer treatments.